Platinum and palladium nanoparticle‐containing mixture, PAPLAL, does not induce palladium allergy. Issue 9 (31st July 2019) - Shibuya, Shuichi; Watanabe, Kenji; Tsuji, Gaku; Ichihashi, Masamitsu; Shimizu, Takahiko
Abstract: Palladium (Pd) is a common metal found in jewellery and dental appliances, but it has been shown to be likely to cause metal allergy. We previously reported that platinum (nPt) and palladium (nPd) nanoparticle‐containing mixture (PAPLAL) has both superoxide dismutase and catalase activities and that the topical application of PAPLAL improved skin atrophy induced by chronic oxidative damage in an ageing mouse model. However, the safety of PAPLAL for preventing Pd allergy remains unclear. In the present study, we investigated whether or not PAPLAL induces Pd allergy. We found that PAPLAL treatment caused no skin inflammation, while nPd administration caused only slight skin inflammation compared to the palladium chloride‐induced severe reaction in an experimental metal allergy model. A gene expression analysis revealed that PAPLAL treatment significantly suppressed the expression of Inf‐γ, Il‐1β and Tnfα genes. Even in human clinical trials using patches containing metal nanoparticles, nPd and PAPLAL failed to induce significant skin inflammation. These results suggest that mixing with nPt in PAPLAL suppresses the inflammation response of nPd. PAPLAL can be expected to be applied to various skin treatments as a safe topical substance.